ANALISIS DAMPAK DESENTRALISASI FISKAL DAN PERTUMBUHAN EKONOMI TERHADAP KESENJANGAN DI KABUPATEN/KOTA PROVINSI JAWA TENGAH - Hadi Sasana (AKSES: Jurnal Ekonomi dan Bisnis, 2009)
In the autonomy and fiscal decentralization era, local governments is provided with authority to increase their income and to conduct allocative function in setting priority of local development.  This research is intended to examine the influence of fiscal decentralization, on economic growth and inter-regional inequality, at  regencies/municipalities level in Central Java Province.Research population consist of 29 regencies and 6 municipalities, employing secondary data from Central Bureau of Statistic of Central Java Province and regencies/municipalities level in Central Java Province within the period of 2001 up to  2005.  Data analysis is conducted by using path analysis with SPSS program software. The results of this study indicate that, fisrt fiscal decentralization has a positive and significant effect on economic growth at regencies/municipalities level in Central Java Province. Second, fiscal decentralization has a negative and significant effect on inter-regional inequality at regencies/municipalities level in Central Java Province. Third, economic growth has a negative and significant effect on inter-regional inequality at regencies/municipalities level in Central Java ProvinceKeywords: fiscal decentralization, economic growth,  inter-regional inequality